The Function of Humanist Expressive Speech Acts of Public Figures in the Covid-19 Outbreak - Areni Yulitawati Supriyono; Ida Zulaeha; Tommi Yuniawan; Carolina Sasabone (Universitas Negeri Semarang, 2024)
The purpose of this study is to analyze the function of expressive humanist speech of public figures in the Covid-19 outbreak on YouTube. The research method used is descriptive qualitative. The sources of research data are the speech acts of public figures during the Covid-19 outbreak on YouTube. The data used is the speech acts of public figures who allegedly contained humanist expressive speech during the Covid-19 outbreak. The results of this study show that from sixteen transcriptions of videos of public figures during the Covid-19 pandemic on YouTube, 123 expressive humanist speech acts were found. A total of 15 expressive speech functions can be analyzed from this data. These functions include saying congratulations, gratitude, sympathy, praise, apologize, criticize, suggest, blame, educate, complain, disappoint, motivate, hope, empathize, and be grateful. The tendency of expressive humanist speech of public figures based on the percentage of frequency, 20% motivating, 18% educating, and 11% sympathetic. The other speech functions are at a percentage below 10%. Public figures have a role in disseminating information and need to be careful so as not to cause social conflict. The function of speech to motivate, educate, and be sympathetic is a function of speech that can be used by public figures in delivering information so that misunderstandings do not occur.